The Role of Neurophysiological Biomarkers in Obsessive-Compulsive Disorder - Herzog, Samuel A; Brakoulias, Vlasios (Current Medicinal Chemistry, 2022)
Background: Obsessive-compulsive disorder is a highly debilitating psychiatric disorder with a high rate of treatment resistance. Biomarkers for obsessive-compulsive disorder may assist clinicians by predicting response to treatments and prognosis. Objective: The aim of the study was to review the literature with regards to two of the more easily ascertainable and relatively inexpensive physiological biomarkers, i.e., heart rate variability and electroencephalography. Methods: A narrative review of the literature was conducted. Results: Decreased heart rate variability has been associated with increased symptom severity of obsessive-compulsive disorder. Findings from electroencephalography have also predicted response to pharmacotherapy and it is likely that biomarkers for OCD will have their greatest utility in predicting response to different pharmacological agents. However, the number of studies is small and results are inconsistent. Conclusion: More research is required to determine whether heart rate variability and electrophysiological studies play a clinical role as biomarkers for obsessive-compulsive disorder.
Keywords: electroencephalography